In Vivo Evaluation of Histopathological Alterations and Trace Metals Estimation of the Small Intestine in Bisphenol A-Intoxicated Rats. (9th December 2019) - Ambreen, Saira; Akhtar, Tasleem; Hameed, Naila; Ashfaq, Isbah; Sheikh, Nadeem
Abstract : BPA, a ubiquitously used plasticizer, has become one of the contaminants of emerging concern and causes many serious health implications in humans due to multiple exposure pathways. The current study was aimed at investigating the deformities of structures that arise by exposure of the small intestine to BPA through trace elements estimation of tissues as well as the study of serum profile. Two major groups of Wistar rats were established: one control group and the other experimental group, which was further divided into four groups based on dose (10 mg/kg/bodyweight and 25 mg/kg/bodyweight, respectively) and duration of exposure (6 and 12 weeks, respectively). Histological study of the small intestine showed the distorted structures in the experimental groups. The special staining performed illustrated the accumulation of calcium deposits in the small intestinal tissue in treated groups. Trace metals estimation showed a significant increase in the metallic content of sodium and iron and a decrease in the calcium content in the experimental groups (p = 0.05 ). Serum profiling illustrated an increase in total iron-binding capacity and glucose levels and a decrease in the serum total iron level (p = 0.05 ). An increased expression of a proinflammatory cytokine (IFN- α ) was observed in the liver. From all these findings, it was inferred that BPA caused many structural alterations in the small intestinal tissue, which further affected its functioning. The calcium deposits seen through special staining affected the motility of the small intestine and caused its dysfunction. It was also induced from serum profiling that BPA affected the homeostasis of iron and glucose and caused its imbalance. Also, as BPA got absorbed from the small intestine and reached the liver via the blood stream, it caused hepatoxicity in the liver and led to increased inflammatory response by IFN- α against the toxicant.